THE ROLE OF EDUPRENEURSHIP ON STUDENTS' ENTREPRENEURIAL INTEREST - Ahmad Riyadissolihin; Syamsul Wathoni; M. Ja’far Shodiq; Lalu Rahmat Sugiara; Zulhaji Ismail; Hafisuddin Aritonang; Yesika Alfianingsih (JURNAL EDUSCIENCE, 2026)
Purpose- This study aims to analyze the role of the Edupreneurship course in shaping the entrepreneurial interest of Master of Arabic Language Education students of UIN Sunan Kalijaga. The primary focus is to describe how students perceive this learning, so that it influences their motivation, mindset, and readiness to pioneer a business in the field of education.Methodology – This study employed a mixed-methods approach with a sequential explanatory design. The research participants were 30 second-semester students in the Master’s Program in Arabic Language Education at UIN Sunan Kalijaga who had completed the Edupreneurship course. Quantitative data were collected through a Likert-scale questionnaire (1–5) to measure students’ perceptions of edupreneurship learning. In contrast, qualitative data were obtained through semi-structured interviews to deepen and explain the quantitative findings. Quantitative data were analyzed using descriptive and inferential statistics, whereas qualitative data were analyzed using thematic analysis.Findings – Students show a strong tendency toward positive perceptions. The majority of respondents chose the agree and strongly agree categories for all indicators, especially those related to increasing entrepreneurial motivation, confidence, independence, and a change in mindset from job seekers to job creators. The interview results reinforce this through narratives about the encouragement to start a business, strengthening competencies, and the benefits of hands-on practice. However, some respondents argued that the lack of mentoring, facilities, and the scope of the material were too narrow, resulting in uneven experience.Contribution – Research contributes to strengthening the curriculum, refining learning strategies, and developing an academic ecosystem that supports the birth of innovative graduates to meet the demands of today's world of work.